Pulmonary lymphangiectasia a rare cause of chylothorax: A case report - Conner, James; Mahon, Richard; Camps, Juan (Journal of Neonatal Surgery, 2022)
Background: Pulmonary lymphangiectasia (PL) is a rare disease characterized by dilation of the pulmonary lymphatic vessels. PL should be considered in the differential diagnosis in infants with pleural effusion, especially in the presence of chylothorax. Case Presentation: A 3-week-old neonate presented with tachypnea, cough, and reluctance to feed. Work-up found bilateral chylous pleural effusion. The patient was initially managed conservatively with bilateral tube thoracostomies and octreotide, however output from chest tubes did not subside. A left thoracotomy was performed with wedge biopsy of the apical segment of the left inferior lung lobe and multiple titanium clips were used to control thoracic duct. Postoperatively the patient continued to have high chest tube output, despite placement of clips. Histology of the biopsy confirmed the diagnosis of congenital pulmonary lymphangiectasia. Conclusion: Pulmonary lymphangiectasia is a rare cause of chylothorax. The treatment is often challenging as found in the index case.